Analisis Ketersediaan Air Upaya Pemenuhan Kebutuhan Air Bersih di Desa Tinawun Kecamatan Malo Kabupaten Bojonegoro - Mushthofa, Mushthofa; Candrasasi, Dian; Roehman, Fatchur (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2023)
Water is a vital need for the survival of every creature on earth. Without water on earth, life would never exist. The level of water demand in each area is definitely different due to the level of use and the number of residents in the area. Likewise, the need for clean water in Bojonegoro Regency varies in each region, including in Tinawun Village, Malo District, Bojonegoro Regency. The purpose of this research is to find out the estimated population of Tinawun Village in 2030 associated with the need for clean water in Tinawun Village in 2030. The calculation method uses arithmetic, geometric and linear regression. The results of this study are that the population of Tinawun Village in 2030 is predicted to be 1,867 people, while the number of customers using WISLIC water in 2030 is estimated to be 124 SRs or an estimated 1,275 people. Prediction of water needs for Tinawun Village based on the number of predicted population in 2030 is 1.789 Liters/second. For predictions of water needs based on the number of customers in 2030 it is 0.955 liters/second. Meanwhile, the availability of water in Sendang Sejahtera, from the research results, is 0.919 liters/second, so that to meet water needs in 2030, there will be a water shortage of 0.036 liters/second.